2011
DOI: 10.5114/aoms.2011.23419
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sonographic criteria in the decision for surgical treatment in infantile hypertrophic pyloric stenosis

Abstract: IntroductionAbdominal ultrasonography has replaced barium studies in establishing the diagnosis in difficult cases of infantile hypertrophic pyloric stenosis (IHPS). The aim of this retrospective study was to establish sonographic criteria of qualification for surgical treatment in children with IHPS.Material and methodsHundred and fifteen infants (98 boys and 17 girls) with suspected IHPS were treated between 2000 and 2009. Pyloric muscle thickness, pyloric diameter and pyloric length were measured in US scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 13 publications
(16 reference statements)
1
20
0
2
Order By: Relevance
“…Ultrasonographic imaging had a sensitivity of 98%, specificity of 100% with a positive predictive value of 100% and 90% respectively [21], which is approximately similar to present study results. The ultrasound, sensitivity and specificity were (97.1%) and (97.4%) respectively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Ultrasonographic imaging had a sensitivity of 98%, specificity of 100% with a positive predictive value of 100% and 90% respectively [21], which is approximately similar to present study results. The ultrasound, sensitivity and specificity were (97.1%) and (97.4%) respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Doyle D mentioned in his study male to female ratio of 4.06:1, while Jerzy Niedzielski, et al mentioned ratio of 8.6:1 [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal ultrasonography has replaced barium studies in establishing the diagnosis in difficult cases of HPS and has become the diagnostic method of choice for HPS over the last 20 years. A pyloric muscle thickness greater than 3 mm was found in all cases of HPS 6. Ultrasound imaging had sensitivity ranging from 76% to 100% and specificity from 85% to 100% 6 7…”
Section: Discussionmentioning
confidence: 94%
“…A pyloric muscle thickness greater than 3 mm was found in all cases of HPS 6. Ultrasound imaging had sensitivity ranging from 76% to 100% and specificity from 85% to 100% 6 7…”
Section: Discussionmentioning
confidence: 94%
“…In the cross-sectional study of Alehossein et al [12], the mean PMT, PL and PD with their range values were 4.94±0.65 mm (range: 3-6.5 mm), 20.22±2.33 mm (range: 16-28 mm) and 13.14±1.97 mm (range: 8.7-17 mm), respectively. Niedzielski et al [32] reported their mean PMT, PL and PD as 5.41 mm, 20.89 mm and 14.1 mm, respectively. In our study, pyloric measurements were close to those mentined above.…”
Section: Discussionmentioning
confidence: 99%